2018
DOI: 10.3390/w10111637
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Crop Production Decisions and Economic Irrigation Water Use Efficiency: The Effects of Water Costs, Pressure Irrigation Adoption, and Climatic Determinants

Abstract: In an irrigated multi-crop production system, farmers make decisions on the land allocated to each crop, and the subsequent irrigation water application, which determines the crop yield and irrigation water use efficiency. This study analyzes the effects of the multiple factors on farmers’ decision making and economic irrigation water use efficiency (EIWUE) using a national dataset from the USDA Farm and Ranch Irrigation Survey. To better deal with the farm-level data embedded in each state of the U.S., multil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 64 publications
(130 reference statements)
1
5
0
Order By: Relevance
“…At a very low irrigation level, the water in the soil will not reach the environment required for the growth of lettuce, thus forming soil water deficit and affecting its growth rate. This finding is consistent with the results of previous studies [31,32]. The results of growth physiological parameters of leaf-expansion lettuce in the first season and heading lettuce in the second season showed that the E and g sc of lettuce in the second season were lower than those in the first season.…”
Section: Discussionsupporting
confidence: 93%
“…At a very low irrigation level, the water in the soil will not reach the environment required for the growth of lettuce, thus forming soil water deficit and affecting its growth rate. This finding is consistent with the results of previous studies [31,32]. The results of growth physiological parameters of leaf-expansion lettuce in the first season and heading lettuce in the second season showed that the E and g sc of lettuce in the second season were lower than those in the first season.…”
Section: Discussionsupporting
confidence: 93%
“…It is easy to fully express the amounts of irrigation water referred to above W m , W l , W w , regardless to the formula of both the productivity function or the cost function, but there is a great difficulty in fully expressing each of the water quantities W el and W ew . So the research presented equations (12) and (15) or figures (2) and (3) where through them and amounts of water W el and W ew can be easily found depending on the amount of water W m , W l , W w .…”
Section: Resultsmentioning
confidence: 99%
“…Water stress negatively affects plants. Depending on the degree and extent of water deficit stress, plants growth and the physiological functions can be limited and affected [2], [3].…”
Section: Introductionmentioning
confidence: 99%
“…Two studies provide additional perspectives on sustainable water use practices using multilevel models and virtual water trade assessments. Using multilevel linear regression models (MLMs), Fan et al's (2019) [16] study analyzed the effects of multiple factors on farmers' decision making and economical irrigation water use efficiency (EIWUE) in a multi-crop production system. The study was conducted across five regions, encompassing 48 states in the USA (Western, Plains, Midwestern, Southern, and Atlantic states) with different cropping patterns and climatic conditions.…”
Section: Content Of the Special Issuementioning
confidence: 99%